Biopsy of the olfactory epithelium from the superior nasal septum: is it possible to obtain neurons without damaging olfaction? - Garcia,Ellen Cristine Duarte (2022)
Abstract Introduction Olfactory epithelium biopsy has been useful for studying diverse otorhinolaryngological and neurological diseases, including the potential to better understand the pathophysiology behind COVID-19 olfactory manifestations. However, the safety and efficacy of the technique for obtaining human olfactory epithelium are still not fully established. Objective This study aimed to determine the safety and efficacy of harvesting olfactory epithelium cells, nerve bundles, and olfactory epithelium proper for morphological analysis from the superior nasal septum. Methods During nasal surgery, 22 individuals without olfactory complaints underwent olfactory epithelium biopsies from the superior nasal septum. The efficacy of obtaining olfactory epithelium, verification of intact olfactory epithelium and the presence of nerve bundles in biopsies were assessed using immunofluorescence. Safety for the olfactory function was tested psychophysically using both unilateral and bilateral tests before and 1 month after the operative procedure. Results Olfactory epithelium was found in 59.1% of the subjects. Of the samples, 50% were of the quality necessary for morphological characterization and 90.9% had nerve bundles. There was no difference in the psychophysical scores obtained in the bilateral olfactory test (University of Pennsylvania Smell Identification Test [UPSIT®]) between means before biopsy: 32.3 vs. postoperative: 32.5, p= 0.81. Also, no significant decrease occurred in unilateral testing (mean unilateral test scores 6 vs. 6.2, p= 0.46). None out of the 56 different odorant identification significantly diminished (p> 0.05). Conclusion The technique depicted for olfactory epithelium biopsy is highly effective in obtaining neuronal olfactory tissue, but it has moderate efficacy in achieving samples useful for morphological analysis. Olfactory sensitivity remained intact.